The diagnostic accuracy of an initial point-of-care lactate at the emergency department as a predictor of in-hospital mortality among adult patients with sepsis and septic shock - Gicheru, Brenda; Shah, Jasmit; Wachira, Benjamin; Omuse, Geoffrey; Maina, Daniel (Frontiers in Medicine, 2023)
Background In patients with sepsis, elevated lactate has been shown to be a strong predictor of in-hospital mortality. However, the optimal cutoff for rapidly stratifying patients presenting to the emergency department at risk for increased in-hospital mortality has not been well defined. This study aimed to establish the optimal point-of-care (POC) lactate cutoff that best predicted in-hospital mortality in adult patients presenting to the emergency department. Methods This was a retrospective study. All adult patients who presented to the emergency department at the Aga Khan University Hospital, Nairobi, between 1 January 2018 and 31 August 2020 with suspected sepsis or septic shock and were admitted to the hospital were included in the study. Initial POC lactate results (GEM 3500® blood gas analyzer) and demographic and outcome data were collected. A receiver operating characteristic (ROC) curve for initial POC lactate values was plotted to determine the area under the curve (AUC). An optimal initial lactate cutoff was then determined using the Youden Index. Kaplan–Meier curves were used to determine the hazard ratio (HR) for the identified lactate cutoff. Results A total of 123 patients were included in the study. They had a median age of 61 years [interquartile range (IQR) 41.0–77.0]. Initial lactate independently predicted in-hospital mortality [adjusted odds ratio (OR) 1.41 95% confidence interval (CI 1.06, 1.87) p = 0.018]. Initial lactate was found to have an area under the curve (AUC) of 0.752 (95% CI, 0.643 to 0.86). Additionally, a cutoff of 3.5 mmol/L was found to best predict in-hospital mortality (sensitivity 66.7%, specificity 71.4%, PPV 70%, NPV 68.2%). Mortality was 42.1% (16/38) in patients with an initial lactate of ≥ 3.5 mmol/L and 12.7% (8/63) in patients with an initial lactate of <3.5 mmol/L (HR, 3.388; 95% CI, 1.432–8.018; p < 0.005). Discussion An initial POC lactate of ≥ 3.5 mmol/L best predicted in-hospital mortality in patients presenting with suspected sepsis and septic shock to the emergency department. A review of the sepsis and septic shock protocols will help in the early identification and management of these patients to reduce their in-hospital mortality.